The Influence of Word of Mouth and Brand Image on Consumers' Decisions to Choose Umrah Tour and Travel Services At PT. Al-Shafwah Independent Tourism Smarts Umrah Palembang - Widra Rahayu Farka; Sulastri Sulastri (International Journal of Social Service and Research, 2023)
This study aims to determine the influence of word of mouth and brand image on consumer decisions to choose Umrah tour and travel services at PT. Alshafwah Wisata Mandiri Smarts Umrah Palembang. The population in this study is all pilgrims who depart with Smarts Umrah Palembang travel. The sampling technique used in this study was a random sampling method with inclusion criteria with a sample of 130 respondents. The results of multiple linear analysis show that word of mouth and brand image have a positive and significant influence on the consumer decisions of Smarts Umrah Palembang pilgrims. Word of mouth, want to promote sustainably by rewarding pilgrims who want to become agents by promoting Smarts Umrah travel service programs and following promotional trends in order to expand consumer reach. Brand Image, it is expected that Smarts Umrah will give coupons for Umrah fee discounts or even give gifts of Umrah service products for free at an event, especially religious events so that Smarts Umrah travel is increasingly discussed by consumers and potential customers.